(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
"Technology" is a Greek word, "technos" means skill, art, "logos" means science, doctrine. The concept of ‘technology’ is defined as a set of methods and techniques used in production processes to obtain a finished product and as a science that produces and improves such methods and techniques.